Več kot pol stoletja po podpisu avstrijske državne pogodbe ostaja problem dvojezičnih "označb in napisov topografskega značaja" na avstrijskem Koroškem nerešen - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
Austria is in accordance with Paragraph 3 of Article 7 of Austrian State Treaty of 1955 obliged to solve the problem of bilingual Ćtopographical terminology and inscriptionsĆ on the territory of autochthonous settlement of Slovene minority in southern Carinthia. The problem remains unsolved until now a day. The two attempts to solve the problem in 1955 (an attempt to installa sign-post in commune of Moos bei Bleiburg/Blato pri Pliberku) and an attempt to put into effect the law on bilingual topographic signs of 1972 remained unfulfilled. Decree of 1977 on the basis of which bilingual topographic signs would be posted in 91 settlements in eight communes of southern Carinthia was only partially fulfilled. Until 2000 ca. 70 bilingual signs were erected. Due to the fact that Decree conditioned erection of bilingual signs with 25-percent of minority population, many Carinthian Slovenes complained to Constitutional Court. On the basis of one of those complaints, Austrian Constitutional Court decreed 25-percent of minority population as an obligatory condition to erect bilingual localities signs as unconstitutional. On the basis of this decision it became clear that Austrian government shall have to find a new solution. In spite of numerous attempts of Austrian federal government to find a solution with representatives of Slovene minority, provincial Carinthian government and representatives of local governments in southern Carinthia also attempts of Austrian governments of 2006 and 2007 did not solve the problem of bilingual 'topographical terminology and inscriptions' in southern Carinthia.
Keywords: Austria; Avstrija; narodne manjšine; koroški Slovenci; Carinthian Slovenes; pravno varstvo; krajevni napisi; dvojezični krajevni napisi; avstrijska državna pogodba